Phase pure Ni3S2 and NiS from bis(N′-ethyl-N-piperazinylcarbodithioato-S, S′)–nickel(ii) via solvent thermolysis and aerosol assisted chemical vapour deposition. (26th March 2018) - Gervas, Charles; Mlowe, Sixberth; Akerman, Matthew P.; Revaprasadu, Neerish
Abstract : We report the structure of a triclinic bis( N ′-ethyl- N -piperazinylcarbodithioato- S, S ′)–nickel(ii ) complex and its use as a single source precursor for the synthesis of nickel sulfide thin films and nanoparticles. Abstract : A bis( N ′-ethyl- N -piperazinylcarbodithioato- S, S ′)–nickel(ii ) complex was prepared and characterized using infrared spectroscopy, thermogravimetric and elemental analyses. The crystal X-ray structure for bis( N ′-ethyl- N -piperazinylcarbodithioato- S, S ′)–nickel(ii ) was determined. The complex was subsequently used as a single source precursor (SSP) for the synthesis of phase pure Ni3 S2 and NiS nanoparticles and thin films via hot injection thermolysis and aerosol assisted chemical vapour deposition (AACVD) routes, respectively. For the hot injection thermolysis route, hexadecylamine (HDA) and oleylamine (OLA) were used as capping groups at varying temperatures. Chloroform was used as the solvent in the AACVD experiments. Powder X-ray revealed that the capping group does not change the phase of nanoparticles formed whereas the AACVD technique produced different phases. Variation of temperature did not affect the phase purity of the nanomaterials formed. The morphology of the thin films obtained via AACVD depended largely on the deposition temperature, whereas for the nanoparticles, temperature and the capping group had a significant impact.